MULTIMODAL CONCEPTUAL METAPHOR IN POLITICAL MEDIA DISCOURSE - Shevchenko, Iryna (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. This article addresses the multimodal conceptual metaphor in the modern English and Ukrainian political media discourse. Purpose. The purpose of this study is to identify the cognitive-semiotic mechanisms of metaphorical construction of discourse-generating concepts of political discourse in social networks. To reach this aim, an immediate task of this research is to describe the concept of WAR and related concepts of UKRAINE, PARTNERS OF UKRAINE, RUSSIA presented through visual and audial modes by verbal, graphic, and cinematic semiotic resources. The material for the analysis was drawn from the news discourse of American and Ukrainian Telegram channels, which cover the course of the Russia-Ukraine war for the period from spring 2022 to spring 2024. Results. This present study helped clarify the methodological principles of the formation of a multimodal conceptual metaphor. The research made it possible to single out mechanisms of cross-mapping underlying the multimodal conceptual metaphor of WAR as an effective way of influencing the users’ world construals by verbal, visual, and cinematic semiotic resources in the posts of news telegram channels. Originality. The novelty of this study lies in the choice of its object, subject, and material, as well as a cognitive-semiotic framework of their analysis. Today, a cognitive-semiotic approach to the online media discourse opens up new perspectives for political linguistics. Conclusions. In the posts Ukrainian and English telegram news channels, both verbal and visual semiotic resources are able to construct conceptual metaphors of WAR, The mechanism of multimodal construction of conceptual metaphors of WAR is related to conceptual metonymy. I claim that in the muiltimodal media discourse, the target concept of WAR and source elements involved in the process of cross-mapping can belong to the same or different semiotic systems, thus forming a verbal or hybrid visual-verbal conceptual metaphor